Evaluation of a bioengineered construct for tissue engineering applications. Issue 6 (11th November 2017) - Ayala, Perla; Dai, Erbin; Hawes, Michael; Liu, Liying; Chaudhuri, Ovijit; Haller, Carolyn A.; Mooney, David J.; Chaikof, Elliot L.
Abstract: Effective biomaterial options for tissue repair and regeneration are limited. Current biologic meshes are derived from different tissue sources and are generally sold as decellularized tissues. This work evaluated two collagen based bioengineered constructs and a commercial product in a model of abdominal full thickness defect repair. To prepare the bioengineered construct, collagen type 1 from porcine skin was isolated using an acid solubilization method. After purification, the collagen was formed into collagen sheets that were physically bonded to form a mechanically robust construct that was subsequently laser micropatterned with pores as a means to promote tissue integration (collagen only construct). A second engineered construct consisted of the aforementioned collagen construct embedded in an RGD‐functionalized alginate gel that serves as a bioactive interface (collagen‐alginate construct). The commercial product is a biologic mesh derived from bovine pericardium (Veritas ® ). We observed enhanced vascularization in the midportion of the engineered collagen‐alginate construct 2 weeks after implantation. Overall, the performance of the bioengineered constructs was similar to that of the commercial product with comparable integration strength at 8 weeks. Bioengineered constructs derived from monomeric collagen demonstrate promise for a variety of load bearing applications in tissue engineering. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 2345–2354, 2018.